ChemInform Abstract: Synthesis of γ‐Nitroaldehydes Containing Quaternary Carbon in the α‐Position Using a 4‐Oxalocrotonate Tautomerase Whole‐Cell Biocatalyst. Issue 17 (April 2015) - Radivojevic, Jelena; Minovska, Gordana; Senerovic, Lidija; O'Connor, Kevin; Jovanovic, Predrag; Savic, Vladimir; Tokic‐Vujosevic, Zorana; Nikodinovic‐Runic, Jasmina; Maslak, Veselin
Abstract The resulting γ‐nitroaldehydes exhibit moderate antifungal activity and mild in vitro cytotoxicity against human fibroblasts.